Without regard to good manners a biography of Gilbert Stuart 1743 - 1786 - Zachs, William (Edinburgh Univ. Press, 1992)
This is the first biography of Gilbert Stuart, an important figure in the Scottish Enlightenment. His bold challenge to the ideas of David Hume, his innovative style of literary criticism and his passionate defence of Mary Queen of Scots were controversial and well known in his day but have since been forgotten. This study incorporates Stuart's own writings, manuscript sources and contemporary accounts to recount the life of a rebellious and idiosyncratic man. In this enjoyable biography Stuart's career is located within the context of eighteenth-century literary and political history. Zachs sets out the development of Stuart's controversial approach and describes how he returned to his native Scotland, after gaining hard won recognition on London's Grub Street. The periodical Stuart founded did not succeed, but it established a critical approach which was taken up by nineteenth-century reviewers. His brand of historical writing anticipated the romanticism of the next generation. After failing to earn the acclaim he believed was his due, Stuart ended his life a disappointed man, steeped in alcohol and suffering physical and mental self-destruction yet still fighting his adversaries to the end.
Keywords: Stuart, Gilbert <1743-1786>; Stuart, Gilbert <1742-1786>; Geschichte 1700-1800; Critics -- Scotland -- Biography; Historians -- Scotland -- Biography; Schottland; Scotland -- Historiography; Scotland -- Intellectual life -- 18th century; Biografie; Stuart, Gilbert